2022
DOI: 10.5603/fm.a2021.0067
|View full text |Cite
|
Sign up to set email alerts
|

Persistent trigeminal artery as a rare cause of vertebrobasilar insufficiency

Abstract: The persistent trigeminal artery (PTA) is the most common fetal carotid-basilar anastomosis which may persist into adult life. In the literature there are numerous papers referring to the anatomical characteristics of this anomalous vessel. In the majority of cases PTA is an incidental finding and its clinical significance has been debated. Some authors describe the coincidence of PTA with various clinical syndromes. However, there are few reports linking PTA with the symptoms of vertebrobasilar insufficiency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…PTA is mostly asymptomatic. However, in the literature, pathological conditions, such as aneurysms, vascularnerve compression, trigeminal cavernous fistulas, and thromboembolic ischemia, as well as associated neurological conditions, palsies of the third sixth cranial nerves, trigeminal neuralgia, vertigo, ataxia, migraine, and headache have been described in patients with this variation (2,4). In this report, we present a case of PTA variation with multiple foci of infarction in the posterior arterial system irrigation area and no arterial occlusion.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…PTA is mostly asymptomatic. However, in the literature, pathological conditions, such as aneurysms, vascularnerve compression, trigeminal cavernous fistulas, and thromboembolic ischemia, as well as associated neurological conditions, palsies of the third sixth cranial nerves, trigeminal neuralgia, vertigo, ataxia, migraine, and headache have been described in patients with this variation (2,4). In this report, we present a case of PTA variation with multiple foci of infarction in the posterior arterial system irrigation area and no arterial occlusion.…”
Section: Introductionmentioning
confidence: 83%
“…PTA is the most common variation of the four wellknown embryological primitive anastomoses between the carotid and vertebrobasilar systems and can be accompanied by vascular pathologies, such as stenosis, occlusion, and dissection and vascular variations, such as the congenital absence of ICA (2,5,6). In addition, this variation may be a cause of vertebrobasilar insufficiency (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K. Sulima reported a case of VBA insu ciency caused by PTA. 17 Also, Daiki Watanabe found that the PTA was associated with ipsilateral hypoplasia of ICA. 21 PTA related carotid cavernous stula, 9 aneurysm, 4,20 and arteriovenous malformation 9 were also reported.…”
Section: Discussionmentioning
confidence: 99%